2021
DOI: 10.1002/alz.12325
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related calcium dysregulation linked with tau pathology and impaired cognition in non‐human primates

Abstract: Introduction:The etiology of sporadic Alzheimer's disease (AD) requires nongenetically modified animal models. Methods:The relationship of tau phosphorylation to calcium-cyclic adenosine monophosphate (cAMP)-protein kinase A (PKA) dysregulation was analyzed in aging rhesus macaque dorsolateral prefrontal cortex (dlPFC) and rat primary cortical neurons using biochemistry and immuno-electron microscopy. The influence of calcium leak from ryanodine receptors (RyRs) on neuronal firing and cognitive performance was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
82
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 69 publications
(99 citation statements)
references
References 56 publications
3
82
2
Order By: Relevance
“…While the lack of neuron loss in all other analyzed areas seems to indicate that rhesus macaques do not naturally lose neurons as they age, it is interesting to note that the multiple cohorts of rhesus monkeys have shown p-tau tangles in the hippocampus (i.e., Paspalas et al, 2018;Datta et al, 2021). Furthermore, in clinical studies it has been shown that p-tau tangles are associated with cell death-one of the primary drivers of cognitive decline in AD (Peters et al, 1994;Datta et al, 2021). Taken together, the overall consensus is that rhesus macaques do not show the distinctive neuronal loss that characterizes the later stages of AD in humans, and which is associated with dementia.…”
Section: Neuronal Deathmentioning
confidence: 98%
See 4 more Smart Citations
“…While the lack of neuron loss in all other analyzed areas seems to indicate that rhesus macaques do not naturally lose neurons as they age, it is interesting to note that the multiple cohorts of rhesus monkeys have shown p-tau tangles in the hippocampus (i.e., Paspalas et al, 2018;Datta et al, 2021). Furthermore, in clinical studies it has been shown that p-tau tangles are associated with cell death-one of the primary drivers of cognitive decline in AD (Peters et al, 1994;Datta et al, 2021). Taken together, the overall consensus is that rhesus macaques do not show the distinctive neuronal loss that characterizes the later stages of AD in humans, and which is associated with dementia.…”
Section: Neuronal Deathmentioning
confidence: 98%
“…This brain region is highly sensitive to cognitive and pathological aging changes, critical to memory consolidation, and undergoes significant shrinkage in AD (Freeman et al, 2008;Squire et al, 2015). While the lack of neuron loss in all other analyzed areas seems to indicate that rhesus macaques do not naturally lose neurons as they age, it is interesting to note that the multiple cohorts of rhesus monkeys have shown p-tau tangles in the hippocampus (i.e., Paspalas et al, 2018;Datta et al, 2021). Furthermore, in clinical studies it has been shown that p-tau tangles are associated with cell death-one of the primary drivers of cognitive decline in AD (Peters et al, 1994;Datta et al, 2021).…”
Section: Neuronal Deathmentioning
confidence: 99%
See 3 more Smart Citations